2019
DOI: 10.5603/fm.a2018.0085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PECAM-1 and p38 MAPK expressions in cerebellum tissue of rats treated with caffeic acid phenethyl ester: a biochemical and immunohistochemical study

Abstract: Background: This study aimed to investigate the antioxidative and anti-inflammatory effects of caffeic acid phenethyl ester (CAPE) on damage caused to cerebellum tissue by diffuse traumatic head trauma via biochemical, histopathologic, and immuno-histochemical methods. Materials and methods: Male Sprague-Dawley (300-350 g) rats were subjected to traumatic brain injury with a weight-drop device (300 g/1 m weight-height impact). Twenty-four adult rats were randomly divided into three equal groups of 8, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The broad spectrum of pharmacological activities shown by CAPE ranges from anti-oxidant/anti-inflammatory to anti-viral/anti-fungal properties, including anti-proliferative effects in various cancer models [10]. A recent in vivo study indicated that CAPE has the ability to cross the blood-brain barrier in rats [11,12]. This review focuses on the protective effects of CAPE in many diseases that can affect the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…The broad spectrum of pharmacological activities shown by CAPE ranges from anti-oxidant/anti-inflammatory to anti-viral/anti-fungal properties, including anti-proliferative effects in various cancer models [10]. A recent in vivo study indicated that CAPE has the ability to cross the blood-brain barrier in rats [11,12]. This review focuses on the protective effects of CAPE in many diseases that can affect the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused mainly on severe TBI inadulthood [37][38][39]. Given the higher incidence of mild TBI (mTBI) at the age of 10~29 [71], it is therefore in the urgent interest of public health that clinical researchers focus on elucidating the pathological mechanisms of, and devising new therapies for, the neurological, psychological consequences of juvenile mild-TBI (mTBI-J).…”
Section: Discussionmentioning
confidence: 99%
“…Generalized anxiety disorder (GAD), PTSD, and MDD are the most prevalent psychiatric sequelae of TBI. Previous TBI studies have focused mainly on adults [37][38][39], but adolescent males comprise the largest TBI cohort with 21.3% of total cases [40]. Therefore, in the urgent interest of public health, researchers are beginning to focus on elucidating the pathological mechanisms and devising new therapies for the neurological and psychological consequences of adolescent TBI.…”
Section: Introductionmentioning
confidence: 99%
“…CAPE is obtained from propolis honey bee through extraction [ 16 ], the structure of CAPE contains catechol which is a powerful antioxidant [ 17 ]. Propolis has long been used for many years as traditional medicine [ 18 ]. The antioxidant effect of propolis which contain CAPE is stronger if compared to propolis without CAPE [ 17 , 18 ].…”
Section: F2 Isops Are Extremely Stable Compoundsmentioning
confidence: 99%
“…Propolis has long been used for many years as traditional medicine [ 18 ]. The antioxidant effect of propolis which contain CAPE is stronger if compared to propolis without CAPE [ 17 , 18 ]. CAPE has also been reported to inhibit prostaglandin (PG) and leukotriene synthesis.…”
Section: F2 Isops Are Extremely Stable Compoundsmentioning
confidence: 99%